First-principles calculations to investigate the bulk, electronic, optical and thermoelectric properties of BaGe2As2 and BaGe2P2 alloys - Debora Nameme; George S. Manyali; Michael Nakitare Waswa; Job W. Wafula (Results in Materials)
The structural, elastic, electronic, and optical properties of BaGe2As2 and BaGe2P2 have been theoretically investigated, but their thermoelectric properties have not been reported. The current work aimed at conducting an exhaustive study on the bulk, electronic, and optical properties as well as the thermoelectric property of BaGe2As2 and BaGe2P2 zintl phase compounds. Density functional theory implemented in Quantum ESPRESSO code combined with other processing codes such as Thermo−pw and BoltzTrap were employed in this study. The lattice constants computed were found to agree well with the other theoretical and experimental results, demonstrating validity of the study. Both compounds are brittle, elastically anisotropic and mechanically as well thermodynamically stable. The materials in this investigation were discovered to be semiconductors with indirect band gaps of 0.73 eV and 1.14 eV for BaGe2As2 and BaGe2P2 respectively. Therefore, both materials are appropriate for use in the electronics sector, notably in temperature control applications. The PDOS analysis suggests that P and As in BaGe2P2 and BaGe2As2, respectively, dominate the conduction band, whereas Ge dominates the valence band in both cases. The results also show that BaGe2P2 out-performs BaGe2As2 in terms of optical absorption coefficient. Both BaGe2As2 and BaGe2P2 are excellent p-type thermoelectric materials but BaGe2P2 has a greater figure of merit than BaGe2As2, making it a potential thermoelectric material. Lastly, the figure of merit values determined in this study are considered approximations since the lattice thermal conductivities of complex BaGe2As2 and BaGe2P2 compounds were not computed due to limited computational resources.